PSYCHOLOGICAL FACTOR AFFECTING ENGLISH STUDENTS WILLINGNESS TO COMMUNICATE IN ENGLISH IN SOCIAL MEDIA - Saputra, Dwi Ando; Saputra, Eki; Angraini, Ria; Jaya, Sinarman (Yayasan Nuraini Ibrahim Mandiri, 2024)
The objective of the research was to find out pyschological factors and dominant factor affecting English Students′ willingness to communicate in English in Social Media. The design of this research was descriptive method. The instrument of the research was questionnaire based on MacIntyre et al. in Tuyen, Thị, & Loan (2019: 253) psychological factor affecting the students willingness to verbal communicate using English in Social Media and the questionnaire adapted from Chotipaktanasook (2017) research. The result of the research were: there are five psychological factors affecting the seventh semester students willingness to communicate in English in social media they are: Self confidence, Perceived communicative competence, learning anxiety, Students’ motivation and Personality. The dominant psychological factors affecting the seventh semester students willingness to communicate in English in social media is students motivation factor. Afterthat in communicate verbally (oral and written) the students more like or dominant use written communicate because it can make the students more confident. From the result, the researcher will give suggestion for the students: It is suggested the students can be more confident to oral communicate using English in social media. The students also diminish their anxiety to be better communicate orally using English in social media and in their daily life.